Analisis Kekuatan Baja Balok Dan Rel Untuk Konstruksi Mesin Crane - Nabil, Ahmad (Jurnal Vokasi Teknik Sipil, 2023)
According to BPS Statistics for the Manufacturing Industry from 2013 to 2015 there was an increase in the number of manufacturing industries in Indonesia. One of them is the Overhead Crane which is a crane that is often used in workshops, whereas in accidents due to structural failure, according to OSHA, 80% of the main causes of failure are due to overloading. In this UTS assignment, the author wants to analyze the strength of crane beams and crane rails. And on the results of the analysis of the calculation of the strength of the crane beam and crane rail with a stretch of 4.75 meters, the distribution of Va to the crane wheels (Live Load) reaches M max = 0.4126829687600 tons. (Dead Load) M = 0.2972609375 tons/m. (Live load + Dead load) Mux = 7099439.0626 N/mm. has compactness between the Flanges and also the Web, while those that meet the requirements between short, medium and long spans are medium because they meet the requirements ? < ?p < ?r, and the last Mn ? Mp, 335,977,243,544065 ? 2,102,500,000 is said to meet the requirements.